Processo de Bernoulli correlacionado - Novaes, Ricardo De Carli (Universidade Federal de São Carlos, 2019)
The independent Bernoulli process, which is a sequence of independent Bernoulli random variables, is already widely known in the statistical literature. This masters thesis works with a generalization of this process: the correlated Bernoulli process, that is, dependent Bernoulli random variables in which the probabilityof success at time n+1 is a linear function of the number of successes until time n. For this model, we present the Strong Law of Large Numbers, the Central Limit Theorem and Law of the Iterated Logarithm.
Correlated Bernoulli process
Keywords: Processo de Bernoulli correlacionado; Lei Forte dos Grandes Números; Lei do Logaritmo Iterado; Correlated Bernoulli process; Strong Law of the Large Numbers; Law of the Iterated Logarithm; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::FUNDAMENTOS DA ESTATISTICA